Faktor - Faktor Yang Mempengaruhi Real Earnings Management Pada Perusahaan Manufaktur Di BEI - Linda Santioso; Emily Janice; Andreas Bambang Daryatno (Jurnal Ekonomi, 2020)
This research aims to find out and analyze the impact of audit committee financial expertise, audit quality that is proxied by external audit firm size, and profitability on real earnings management. The method used in this research was purposive sampling with a total sample of 59 manufacturing companies listed on the Indonesian Stock Exchange (IDX). The type of data used was secondary data acquired through financial statements extracted from www.IDX.co.id. Data analysis methods used in this research were classical assumption analysis, descriptive statistical test, f test, t-test, and the test of determination coefficient. T-test was used to test this study's hypothesis. The final result of the study showed that audit committee financial expertise and audit quality proxied by external audit firm size do not have any significant effect on real earnings management, while profitability has been shown to have a positive effect on real earnings management.